22.4k views
2 votes
Use what you know about reflections of functions
to match the graph to the function rule.

Use what you know about reflections of functions to match the graph to the function-example-1
User Folorunso
by
4.6k points

1 Answer

4 votes

The answers are :

y = 3ˣ ⇒ b

y = 3⁻ˣ ⇒ a

y = -3ˣ ⇒ c

For y = 3ˣ, we will get a graph that will increase exponentially in the direction of positive y-axis.

For y = 3⁻ˣ, we will get a graph that will decrease exponentially in the direction of positive x-axis.

For y = -3ˣ, we will get a graph that will decrease exponentially in the direction of negative y-axis.

User Hdsenevi
by
5.3k points